2013
DOI: 10.1186/1471-2164-14-607
|View full text |Cite
|
Sign up to set email alerts
|

RNA-seq analyses of gene expression in the microsclerotia of Verticillium dahliae

Abstract: BackgroundThe soilborne fungus, Verticillium dahliae, causes Verticillium wilt disease in plants. Verticillium wilt is difficult to control since V. dahliae is capable of persisting in the soil for 10 to 15 years as melanized microsclerotia, rendering crop rotation strategies for disease control ineffective. Microsclerotia of V. dahliae overwinter and germinate to produce infectious hyphae that give rise to primary infections. Consequently, microsclerotia formation, maintenance, and germination are critically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(101 citation statements)
references
References 59 publications
(106 reference statements)
4
93
0
Order By: Relevance
“…Microsclerotia (MS) play a crucial role in Verticillium disease cycle, and many gene families are involved in MS development, including some C 2 H 2 genes and melanin biosynthesis genes that are differentially expressed during MS formation (Duressa et al, 2013;Xiong et al, 2014). Xiong et al found that most of the genes located in the four LS regions annotated in VdLs.17 were expressed at low or undetectable levels in V. dahliae XS11 during MS formation (Klosterman et al, 2011;Xiong et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Microsclerotia (MS) play a crucial role in Verticillium disease cycle, and many gene families are involved in MS development, including some C 2 H 2 genes and melanin biosynthesis genes that are differentially expressed during MS formation (Duressa et al, 2013;Xiong et al, 2014). Xiong et al found that most of the genes located in the four LS regions annotated in VdLs.17 were expressed at low or undetectable levels in V. dahliae XS11 during MS formation (Klosterman et al, 2011;Xiong et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Although light and electron microscopic examinations have defined the morphological sequence of events in the microsclerotial developmental pathway (see précis in Reference 70 and Figure 1), the molecular mechanisms that direct microsclerotial development remain for the most part uncharacterized. However, with genomics-based studies now coming to the fore, genes involved in this developmental process are coming to light through transcriptional profiling and genome-scale random mutagenesis (19,13,41,70,72).…”
Section: The Molecular Machinery That Directs Microsclerotial Developmentioning
confidence: 99%
“…6A). The expression levels of the hydrophobin gene VDH1, involved in early stage of microsclerotia formation (Klimes and Dobinson, 2006) and five genes sharing strong homology to fungal melanin biosynthesis genes and expressed in developing microsclerotia (Duressa et al, 2013;Xiong et al, 2014) were examined by reverse transcription quantitative PCR analyses. As expected, the expression level of VDH1 was significantly reduced in the DVdCrz1-2 strain but was comparable between wild-type and DVdCrz1_C strains (Fig.…”
Section: Vdcrz1 Confers Tolerance To High Concentrations Of Ca 2+mentioning
confidence: 99%